EPR spectroscopy and structural investigations, of Eu2+-doped chloroborate glass-ceramic. Issue 24 (15th December 2021) - Secu, M.; Kuncser, A.; Negrila, C.; Rostas, A.M.
Abstract: Europium doped (0.1% and 1%) chloroborate BaO–B2 O3 –BaCl2 glass and glass-ceramic with embedded BaCl2 nanocrystals have been synthesised, investigated, and compared with the corresponding nanocrystalline powder. The structural analysis of the glass evidenced ionic bonds characteristic to the glass host structure and compositional changes during the melting. X-ray diffraction and transmission electron microscopy revealed the formation of orthorhombic BaCl2 nanocrystals of about tens on nm in size and a smaller amount of BaB2 O4 nanocrystals. Structural analysis of the Eu 2+ -doped BaCl2 nanocrystals has shown a distortion of the crystalline cell assigned to the growth process, affected by defects and ionic impurities. Photoluminescence spectra of the glass-ceramic revealed Eu 3+ and Eu 2+ luminescent ion species, but only Eu 2+ is incorporated within the BaCl2 nanocrystalline phase. Electron paramagnetic resonance measurements in X-band sustain the presence of Eu 2+ ions. The EPR parameters (g values and hyperfine constants) resulting from the Q-band EPR spectra simulations recorded on glass-ceramic are similar to those in Eu 2+ -doped BaCl2 and confirmed the partial incorporation of Eu 2+ ions within the BaCl2 :Eu 2+ nanocrystals in the glass-ceramics.